Value of monoclonal anti-myeloperoxidase (MPO7) for diagnosing acute leukaemia. Issue 10 (October 1990) - Storr, J; Dolan, G; Coustan-Smith, E; Barnett, D; Reilly, J T
Abstract : The expression of myeloperoxidase (MPO) was studied in 100 cases of acute leukaemia (83 with acute myeloid leukaemia (AML) and 17 acute lymphoblastic leukaemia (ALL) by both a conventional cytochemical method and the immunocytochemical antiperoxidase (APAAP) technique using the monoclonal antibody MPO7. In each case the staining was evaluated by light microscopical examination (percentage of positive cells). Of the 83 cases of AML, 78 (93.9%) were positive for MPO7 compared with 70 (84.3%) by cytochemistry. Antibodies against the myeloid markers CD13 and CD33 were positive in 71 (85.5%) and 70 (84.3%) cases, respectively. Importantly, all cases of ALL were negative for both MPO7 and cytochemical MPO staining even when they were positive for CD13 and CD33. These results indicate that the anti-myeloperoxidase antibody MPO7 is the most sensitive and specific reagent for the diagnosis of AML and should therefore be included in routine immunophenotyping panels.